2005
DOI: 10.1002/qua.20833
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular orbital study of conformational properties of cyclohexyne, cycloheptyne, and cyclooctyne

Abstract: ABSTRACT:The structures and relative energies for the basic conformations of cyclohexyne (1), cycloheptyne (2), and cyclooctyne (3) have been calculated by the HF/ 6-31G*, MP2/6-31G*, and B3LYP/6-31G* methods. The C 2 symmetric twist conformer of 1 is calculated to be more stable than the planar C 2v geometry. Ring inversion of the envelope conformation of 2 takes place via C 2 symmetric twist transition state, which is 34.0 kJ mol Ϫ1 higher than the envelope form. The C 2 symmetric chair conformation of 3 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The conversion energy barrier from twist-boat to chair was calculated to be 21.2 (PBE-D3) and 23.0 kJ mol À1 (CCSD(T)) in electronic energies and 20.2 kJ mol À1 (PBE-D3) in Gibbs energies. These values are in good agreement with a previous MP2/6-31G * study [27] that found 11.7 kJ mol À1 for the energy difference and 25.9 kJ mol À1 for the energy barrier. Furthermore, electron diffraction experiments, [28] force field calculations [29] and a 13 C NMR study showing only four signals [30] also suggest that the twist-boat confor-mation can be neglected over a wide temperature range including room temperature.…”
Section: The Cyclooctyne Moleculesupporting
confidence: 92%
See 1 more Smart Citation
“…The conversion energy barrier from twist-boat to chair was calculated to be 21.2 (PBE-D3) and 23.0 kJ mol À1 (CCSD(T)) in electronic energies and 20.2 kJ mol À1 (PBE-D3) in Gibbs energies. These values are in good agreement with a previous MP2/6-31G * study [27] that found 11.7 kJ mol À1 for the energy difference and 25.9 kJ mol À1 for the energy barrier. Furthermore, electron diffraction experiments, [28] force field calculations [29] and a 13 C NMR study showing only four signals [30] also suggest that the twist-boat confor-mation can be neglected over a wide temperature range including room temperature.…”
Section: The Cyclooctyne Moleculesupporting
confidence: 92%
“…Structural parameters of the optimized molecule in chair conformation are found in Table 2. The CÀC bond lengths and C-C-C angles are in good agreement with previous calculations at the Hartree-Fock/6-31G * level [27] and experimental results. [28] Differences, the largest ones to experiment being 0.062 and 8.18, can be attributed to missing temperature and anharmonicity effects that have not been considered in our calculations as well as the simplified structural model assumed in the data refinement of the experimental study.…”
Section: The Cyclooctyne Moleculesupporting
confidence: 91%
“…Our calculations show that the alkyne ( 1 ) is distorted from linearity by 48°, which is in agreement with past theoretical studies of cyclohexyne using Hartree-Fock, DFT, or Møller-Plesset perturbation theory methods. 1416 The C-C and C-O bond lengths in cyclopentanone enolate ( 2a ) are representative of enolate character. Figure 2 shows the geometries of cyclopentanone enolate nucleophilic addition to cyclohexyne optimized in the gas phase with B3LYP/6-31G(d) and B3LYP/6-311++G(d,p).…”
Section: Resultsmentioning
confidence: 99%
“…Yavari et al investi- gated the possible conformations of cycloheptyne 45, using ab initio calculations. [43] Cycloheptyne has two main geometries: the envelope (C s ) conformation -corresponding to an energy minimum -and the twist-transition state (C 2 ), which corresponds to an energy maximum of 34.0 kJ mol -1 (Figure 4). Krebs and co-workers synthesized compound 45 and other more stable analogues 46 and 47 by irradiation of the corresponding cyclopropenones (Scheme 12).…”
Section: Cycloheptynementioning
confidence: 99%
“…[7,48] It was found that the C-C C-C unit in cyclooctyne is still deformed, with a C C-C angle of 154.5°, with different accessible conformations. Work by Yavari and co-authors [43] showed that the chair conformation with C 2 symmetry is more stable than the twisted conformation. The authors used DFT calculations to investigate the interconversion energy between the two forms.…”
Section: Cyclooctynementioning
confidence: 99%